2017
DOI: 10.1177/0022034517732754
|View full text |Cite
|
Sign up to set email alerts
|

Complex Intratissue Microbiota Forms Biofilms in Periodontal Lesions

Abstract: Periodontitis is caused by dysbiotic subgingival bacterial communities that may lead to increased bacterial invasion into gingival tissues. Although shifts in community structures associated with transition from health to periodontitis have been well characterized, the nature of bacteria present within the gingival tissue of periodontal lesions is not known. To characterize microbiota within tissues of periodontal lesions and compare them with plaque microbiota, gingival tissues and subgingival plaques were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 41 publications
1
43
0
3
Order By: Relevance
“…The characteristics of the intratissue bacterial communities in OLP lesions were quite different from those in periodontitis lesions 11 . The bacterial communities within the gingival tissues had similar alpha diversities but decreased beta diversities compared with the plaque communities.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The characteristics of the intratissue bacterial communities in OLP lesions were quite different from those in periodontitis lesions 11 . The bacterial communities within the gingival tissues had similar alpha diversities but decreased beta diversities compared with the plaque communities.…”
Section: Discussionmentioning
confidence: 75%
“…isolation of E. coli strains from OLP tissues. We previously reported that a key periodontal pathogen, Porphyromonas gingivalis, invades gingival tissues and is highly enriched in the intratissue bacterial communities at periodontal lesions 11,12 . Similarly, a species enriched within the tissues of OLP lesions may have a role in the pathogenesis of OLP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Porphyromonas gingivalis exploits various mechanisms to subvert the host innate immune response and therefore alone it may not induce sufficient inflammation to cause alveolar bone loss. Porphyromonas gingivalis ‐induced alveolar bone loss is dependent on the invasion of periodontal tissues by commensal bacteria . Incorporating the findings from the present study, QSIs could re‐establish bacterial communities within periodontal tissues that are favorable for periodontal health through a reduction of the total bacterial invasion of periodontal tissues.…”
Section: Discussionmentioning
confidence: 52%
“…Patients with acute rheumatic fever had higher levels of serum antibodies that react with ENO1 and bacterial enolase than did patients with streptococcal pharyngitis or healthy control subjects, suggesting the role of streptococcal enolase as a cross-reactive antigen in post-streptococcal autoimmune diseases [23]. The gingival tissues of periodontal lesions are infected with complex bacterial communities, including T. denticola and P. gingivalis , and patients with periodontitis frequently experience bacteremia after tooth brushing or even chewing [24,25]. Although TdEno has the highest homology with ENO1 among the enolases of human-associated bacteria, it is expected that not only TdEno but also the enolases of diverse periodontitis-associated bacteria contribute to the production of anti-ENO1 antibodies in periodontitis.…”
Section: Discussionmentioning
confidence: 99%